How self-leadership promotes job crafting: Based on the perspective of self-determination theory - Liu, Geng; Peng, Huimin; Wen, Hao (Frontiers in Psychology, 2023)
According to self-determination theory, the present study develops a moderated mediation model to investigate how and when self-leadership promotes employees’ job crafting, emphasizing the mediating effect of autonomous motivation and the moderating effect of leader empowering behavior. We analyze and test the hypotheses based on 269 valid three-wave data from employees. The findings show that self-leadership has a significantly positive impact on job crafting, and a positive indirect effect on job crafting via autonomous motivation. Furthermore, leader empowering behavior not only enhances the positive impact of self-leadership on autonomous motivation, but also positively moderates the mediating effect of autonomous motivation in the relationship between self-leadership and job crafting. Practically, our study provides insights into how to promote job crafting. We also propose limitations and directions for future research.